2018
DOI: 10.1007/jhep06(2018)051
|View full text |Cite
|
Sign up to set email alerts
|

AdS-phobia, the WGC, the Standard Model and Supersymmetry

Abstract: It has been recently argued that an embedding of the SM into a consistent theory of quantum gravity may imply important constraints on the mass of the lightest neutrino and the cosmological constant Λ 4 . The constraints come from imposing the absence of any non-SUSY AdS stable vacua obtained from any consistent compactification of the SM to 3 or 2 dimensions. This condition comes as a corollary of a recent extension of the Weak Gravity Conjecture (WGC) by Ooguri and Vafa. In this paper we study T 2 /Z N compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 98 publications
(179 reference statements)
1
53
0
Order By: Relevance
“…An interesting possibility arises which is that the AdS instability conjecture may forbid the existence of this stable AdS vacuum, which translates into bounds on properties of neutrinos. The idea was first raised in [], and studied in detail in []. A particularly striking possibility is that it bounds the neutrino masses by the cosmological constant mν<normalΛ14.It was then pointed out in [] that this could lead to insights into the hierarchy problem since the neutrino masses are naturally tied to the scale of electroweak symmetry breaking.…”
Section: More Swampland Conjecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting possibility arises which is that the AdS instability conjecture may forbid the existence of this stable AdS vacuum, which translates into bounds on properties of neutrinos. The idea was first raised in [], and studied in detail in []. A particularly striking possibility is that it bounds the neutrino masses by the cosmological constant mν<normalΛ14.It was then pointed out in [] that this could lead to insights into the hierarchy problem since the neutrino masses are naturally tied to the scale of electroweak symmetry breaking.…”
Section: More Swampland Conjecturesmentioning
confidence: 99%
“…In particular, in [] it was shown that one must add the Wilson line of the electromagnetic gauge field on the circle to the analysis, and this leads to an instability associated with the electron. In [] a possible way to remove the instability was considered by taking an orbifold compactification. It was then argued that the question of stability of the AdS vacuum would be related to physics of supersymmetry breaking.…”
Section: More Swampland Conjecturesmentioning
confidence: 99%
“…this case that the λ 2 interaction term is no longer gauge invariant, and a charged scalar may only self-interact through V = λ 1 φ * φ φ * φ. Purely from gauge invariance we thus see that a fundamental scalar has no nonplanar self-interaction diagrams in the one-loop correction to its two-point function, and so there is no remnant of strong UV/IR duality to speak of. 15 The question is then whether there are other examples where this strong UV/IR duality does occur, or whether it is perhaps a peculiar feature of real φ n theories on noncommutative spaces. To answer this, we will study in detail another case of especial phenomenological significance: Yukawa theory.…”
Section: The Vector Fields Transform Asmentioning
confidence: 99%
“…While this is powerful information, the extent to which the UV here meddles with the IR is relatively minor -just dictating where one must live in the space of infrared theories. Even so, they have been found to have possible applications to SM puzzles, including the hierarchy problem [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The potential for the Swampland program, and adjacent developments, to explain some of the more puzzling features of the SM has been explored in e.g. [4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%